2015
DOI: 10.1002/jcb.25223
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Related Apoptosis Inducing Ligand (Trail) in Endothelial Response to Biomechanical and Biochemical Stresses in Arteries

Abstract: Shear stress is determined by three physical components described in a famous triad: blood flow, blood viscosity and vessel geometry. Through the direct action on endothelium, shear stress is able to radically interfere with endothelial properties and the physiology of the vascular wall. Endothelial cells (ECs) have also to sustain biochemical stresses represented by chemokines, growth factors, cytokines, complement, hormones, nitric oxide (NO), oxygen and reactive oxygen species (ROS). Many growth factors, cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In the literature, a number of studies have shown that soluble TRAIL is able to induce the activation of some signal transduction pathways, promoting the survival of VSMCs and ECs. TRAIL also exerts a protective effect on the endothelium through its anti-inflammatory properties and the production of local nitric oxide (NO) [8]. Recently, there has been outstanding progress in the development of novel formulations to increase the circulatory half-life of TRAIL, thus improving the biological attributes of TRAIL-based therapies.…”
Section: The Opg/rankl/rank/trail System: Structures Localizationmentioning
confidence: 99%
“…In the literature, a number of studies have shown that soluble TRAIL is able to induce the activation of some signal transduction pathways, promoting the survival of VSMCs and ECs. TRAIL also exerts a protective effect on the endothelium through its anti-inflammatory properties and the production of local nitric oxide (NO) [8]. Recently, there has been outstanding progress in the development of novel formulations to increase the circulatory half-life of TRAIL, thus improving the biological attributes of TRAIL-based therapies.…”
Section: The Opg/rankl/rank/trail System: Structures Localizationmentioning
confidence: 99%
“…In particular, the TNF and TRAIL receptors become activated and initiate both death and pro-survival signaling. 26 By definition, our experimental model of HS produces a period of ischemia followed by a reperfusion event. Using this model, our laboratory has shown a direct correlation between apoptotic signaling and HS-induced vascular hyperpermeability.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to OPG, TRAIL is present in significantly lower plasma concentrations in people with CAD than in healthy people [6,34,[72][73][74][75]. It is the low plasma concentrations of TRAIL in this group of patients that are associated with a higher risk of CV mortality, a higher risk of post-infarction left ventricular remodelling and the development of HF [6,34,73,[76][77][78]. However, in patients with CAD, it is not only the plasma levels of TRAIL that are relevant.…”
Section: The Combination Of Opg and Trailmentioning
confidence: 99%